Integrated imaging evaluation in infective endocarditis: A pictorial essay on clinical cases of extracardiac complications. (April 2021) - De Stasio, Vincenzo; Delahaye, Francois; Moreau-Triby, Caroline; Pozzi, Matteo; Si-Mohamed, Salim; Douek, Philippe; Boccalini, Sara
Highlights: Extracardiac complications represent a mortality cause of infective endocarditis. Integrated imaging is increasingly necessary for a global assessment of this disease. An overview of IE extracardiac complications at different imaging techniques.